Pushing the limits of deep-ultraviolet scanning near-field optical microscopy - Ryota Ishii; Mitsuru Funato; Yoichi Kawakami (APL Photonics, 2019)
Deep-ultraviolet (DUV) microscopy and microspectroscopy have received much attention in label-free live-cell imaging, selective molecular analysis, and optical characterizations of ultrawide bandgap materials. Far-field optics approaches usually suffer from the diffraction limit of light. Meanwhile, near-field optics technology is immature in the DUV spectral region. Herein, we develop a DUV scanning near-field optical microscope (SNOM) with an excitation wavelength of 210 nm. The fourth harmonic generation of a continuous-wave Ti:sapphire laser is the excitation source. Two negative feedback control systems stabilize the power and pointing, allowing scanning microscopy to be carried out over a long period of time even in the DUV spectral region. A reflective objective couples the excitation beam onto an optical fiber probe. The optical fiber probe is solarization-resistant and is not coated by metallic materials. The reflective-based objective optical design does not introduce chromatic aberrations in the detection signals. Our DUV-SNOM is used to measure the photoluminescence (PL) spectra of the quantum well structure of aluminum gallium nitride, which is an ultrawide bandgap material. The PL mapping images indicate that emissive localization centers can be individually visualized via our DUV-SNOM with a lateral resolution exceeding 150 nm.